The influence of stress and other behavioural factors on the onset and exacerbation of acne - a review of pathogenetic mechanisms, interactions between body systems and directions for therapeutic strategies - Madejska, Maria; Rudzka, Aleksandra; Drzewiecka, Antonina; Drzewiecki, Artur; Korczak, Wiktor; Gaszyńska, Monika; Falkowski, Wojciech; Krysińska, Anna; Woźniak, Weronika; Magielski, Jakub (Quality in Sport, 2025)
Acne vulgaris, which is one of the most common inflammatory skin diseases, affects millions of people worldwide. It is most common during adolescence, but also occurs in adults. Its pathogenesis is the result of a complex interaction of genetic, hormonal, environmental and psychosocial factors. Traditional models have focused on excessive sebum production, impaired keratinisation and colonisation by Cutibacterium acnes. Recent studies show that, in addition to hormonal, genetic and environmental factors, psychological stress is recognised as an important factor influencing the pathogenesis and exacerbation of acne. This review examines the mechanisms by which stress influences the development and severity of acne (considering the role of the skin microbiome, diet and lifestyle), presenting current scientific reports from recent years, and discusses modern therapeutic strategies combining standard pharmacotherapy with mental health support interventions, dietary modification and probiotic therapy.